2009
DOI: 10.1203/pdr.0b013e31818912e7
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Contributions to Disparities in Preterm Birth

Abstract: Ethnic disparity in preterm delivery between African Americans and European Americans has existed for decades, and is likely the consequence of multiple factors, including socioeconomic status, access to care, environment, and genetics. This review summarizes existing information on genetic variation and its association with preterm birth in African Americans. Candidate gene-based association studies, in which investigators have evaluated particular genes selected primarily because of their potential roles in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
82
0
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(86 citation statements)
references
References 73 publications
1
82
0
2
Order By: Relevance
“…Several pathways leading to preterm birth have been outlined, including (1) inflammation, (2) maternal/fetal stress, (3) uterine distension and cervical dysfunction, (4) decidual hemorrhage, and (5) metabolic enzyme variation [5,6]. A modest body of literature has examined the complex genetic contribution to preterm birth [7,8,9], with heritability estimates in the range of 27–36% [10,11]. Several studies have reported associations with single gene variants [12,13,14,15,16,17,18,19,20,21].…”
Section: Introductionmentioning
confidence: 99%
“…Several pathways leading to preterm birth have been outlined, including (1) inflammation, (2) maternal/fetal stress, (3) uterine distension and cervical dysfunction, (4) decidual hemorrhage, and (5) metabolic enzyme variation [5,6]. A modest body of literature has examined the complex genetic contribution to preterm birth [7,8,9], with heritability estimates in the range of 27–36% [10,11]. Several studies have reported associations with single gene variants [12,13,14,15,16,17,18,19,20,21].…”
Section: Introductionmentioning
confidence: 99%
“…Preterm birth has multiple etiologies [2]: there are many maternal or fetal characteristics that have been associated with this disorder, including demographic characteristics, nutritional status such as a low pregnancy body mass index, pregnancy history such as a previous preterm birth and a shorter interpregnancy interval, present pregnancy characteristics such as uterine overdistension due to multiple gestation and polyhydramnios, psychological characteristics and physical abuse, traditional factors or adverse behaviors such as smoking and drinking excess alcohol, as well as routine prepregnancy health promotion [3,4]. Ethnic disparity has also existed, and is likely the consequence of multiple factors, including socioeconomic status and access to public care [5]. The management depends on several variables like gestational age, fetal status and severity of laboratory abnormalities.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, there is a well-described ethnic difference in the rate of PTB (even when controlling for mother contributing etiologic factors). In 2005, the incidence of preterm delivery among African Americans and European Americans in the U.S. was 18.4% and 11.7%, respectively (Anum et al, 2009). This ethnic disparity in PTB between African Americans and European Americans has been present for decades.…”
mentioning
confidence: 99%
“…This ethnic disparity in PTB between African Americans and European Americans has been present for decades. The inequity is likely the consequence of multiple factors, including socioeconomic status, access to care, environment, and differences in genetic background (Anum et al, 2009). …”
mentioning
confidence: 99%